IMPLEMENTASI METODE OUTDOOR LEARNING DAN LATIHAN TERBIMBING PADA PEMBELAJARAN MENULIS PUISI SISWA MADRASAH IBTIDAIYAH - Athfan, Muhammad; Widiyati, Evita (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
This study aims to improve students’ poetry writing skills through the implementation of outdoor learning and guided practice method. Outdoor learning is chosen to provide contextual and inspirational learning experience by utilizing the surrounding environment as a source of ideas for writing poetry. Meanwhile, the guided practice method is used to provide step by step guidance in the writing process, allowing students to develop their writing skills more systematically. This research employs a qualitative approach with a case study design. Data collection is carried out through observation, interviews, and documentation. Data source involve the principal, fourth grade indonesian language teacher, and fourth grade students of MI Al Ma’unah Mojojejer. Data analysis uses source and technique triangulation. The research findings indicate that the combination of outdoor learning and guided practise methods is effective in enhancing students writing skills. Students become more creative in generating ideas, more expressive in composing diction, and more structured in arranging poetry verses. This improvement is evident from the significant increase in poetry writing scores. Therefore, the implementation of these methods can be an effective alternative learning strategy to optimally develop students poetry writing skills.